Are the Clinical Evaluation Scales and Laboratory Tests Adequate in Determining Dehydratation Degree in Acute Diarrhea? - Yaşar Yusuf Can; Medine Ayşin Taşar; Arife Uslu Gökçeoğlu (Galenos Yayinevi, 2022)
Introduction:The aim is to evaluate the reliability of the "World Health Organization dehydration scale (WHODO)", "clinical dehydration scale (CAS)" and "Gorelick scale (GS)" in determining the true degree of dehydration (DH) in children diagnosed with acute diarrhea, together with laboratory tests.Methods:This study was conducted on children aged 3 months to 5 years who were diagnosed with acute diarrhea. Patients' admission weight, clinical findings and urea, creatinine, glucose, sodium, potassium, blood gases, and complete urine test results were recorded; DH grades of the patients were evaluated using WHODO, CAS and GS.The weight recorded within 48-72 hours after discharge was accepted as the actual weight of the patient. The gold standard in determining the degree of DH was considered to be the ratio of the patient's weight at admission to the weight after treatment.Results:One hundred eight children with acute diarrhea were included in the study. WHODO, CAS and GS sensitivity rates, 90%, 52%, 54% for mild DH, 49.4%, 80%, 83% for moderate DH, 96.3%, 86%, 44% for severe DH. Specificity rates are 50%, 75%, 97% in mild DH, 87.5%, 26%, 53% in moderate DH, 44.4%, 73.9% and 96% in severe DH, respectively. In determining patients with DH degree ≥10%, the likelihood ratio of WHODS's positive test result was 11.0, GS's was 14.7. In determining mild DH, the likelihood ratio of the positive test result of GS was found to be 18.0. A significant correlation was found between actual DH degrees and pH, HCO3, creatinine and urine density (p<0.05).Conclusion:It was determined that WHODS and GS were successful in detecting ≥10% dehydration, GS was successful in determining mild dehydration, and situations where the child's weight was not known could be used. We think that pH and HCO3, creatinine and urine density will be useful in determining the degree of dehydration in cases where the child's weight is not known.